Unveiling the Threat of Smartphone Addiction among Female College Students - Rajni Bala (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
The prevalence of smartphone addiction is very common in young generation with the widespread integration of smartphones in to daily life. The purpose of this study was to find out the extent of smartphone addiction among the female college students. An online questionnaire was used to collect the data from 113 female college students. The MS Excel was used to analyze the collected data.  Descriptive statistics were employed to analyze the data in order to derive the final interpretation. The main findings suggested that 35% respondents missed planned work due to smartphone use; 26% respondents feel pain in the wrists or at the back of the neck while using a smartphone; 22% respondents always think about smartphone in their mind even when they are not using it; 17% respondents feel impatient while not holding smartphone; 15% of respondents persistently monitor their smartphones to avoid missing out on conversations happening among others on platforms like Twitter or Facebook.